Quality of life factors affecting quality of life in people living with HIV/AIDS in an urban area - Jadhav, Pradnya S.; Laad, Payal S.; Chaturvedi, R. M. (International Journal Of Community Medicine And Public Health, 2017)
Background: The aims and objectives were to study socio-demographic profile of people living with HIV/ AIDS; to assess quality of life of people living with HIV/AIDS (PLHA); to study factors affecting Quality of life (QOL) in people living with HIV/AIDS. Methods: A cross-sectional study was conducted which included 319 study subjects. Data on socio-demographic profile was collected using questionnaire and quality of life was assessed using WHO - brief questionnaire. Data was analysed using SPSS software and MS–Excel. Results: Majority of study population 52% were female & 40.8%belonged to 35-45 yrs age group. Out of 319 study subjects, 80.88% were literate and 19.1% were illiterates, 75.9% were married. 65.83% of the study subjects belonged to socio-economic class- II, 27.9% of the study subjects belong to class–I. Majority 52.98% study population had CD4 less than 300 and 47.02% had CD4 count more than 300 cells/mm3. Female have better QOl in comparison to male. Subjects >55 age group, illiterate, unemployed and CD4 count <300cells/mm3 have lower QOL (p<0.05) in comparison to their respective group. Conclusions: The most factors significantly associated with decreased quality of life of people living with HIV/AIDS in the present study include gender, literacy status, age group, employment status and CD4 count (p<0.05).